Determinantes do investimento no Brasil - Vieira, Atos Ramon (Universidade do Vale do Rio dos Sinos, 2024)
By checking fluctuations in aggregate income, it is possible to indicate investment as the most important element for economic growth. Investment has an impact both on the supply side (through installed capacity) and on the demand side, when it increases the population's income, providing constant economic growth. In Brazil, we noticed a constant drop in the investment rate (in the investment/GDP ratio), which since the 1990s has had an average of less than 20%. This fact may be related to the instability of Brazilian economic growth. Based on this, the dissertation aims to analyze the determinants of private investment in Brazil in the period from 2001 to 2022. However, the related work will consider how to invest the gross formation of fixed capital, not taking into account variations in stocks. Furthermore, the approach will be in relation to private spending on capital goods, excluding public investment from the analysis, due to its instability. For a better understanding in relation to the demand for investment, we first sought to delve deeper into the main theoretical concepts, in the approaches: traditional, Keynesian and Kalecian. The main works that dealt with the topic of investment determinants were then explained. After this basis, a methodology was developed, which dealt with the estimates and problems of a time series econometric model, in the format of Autoregressive Vectors (VAR), such as the variables selected to compose the aforementioned model. After theoretical and methodological investigations, statistical tests are run to analyze the results. From the impulse-response test, two variables had a corresponding effect on private investment (PRIV): household consumption (CONS) and installed capacity utilization (CAP). On the other hand, it was tested whether there was an effect of the apparent consumption of machinery and equipment (PRIV), on the economic activity level variables (CONS and CAP). The test result showed that variations in household consumption and use of installed capacity reacted to PRIV. Finally, the conclusion of the study proved that the Kaleckian theory is the closest in relation to the determinants of investment, according to the results found.
Keywords: Determinantes do investimento; Consumo das famílias; Utilização da capacidade instalada; Consumo aparente de máquinas e equipamentos; Determinants of investment; Household consumption; Use of installed capacity; Apparent consumption of machines and equipment; ACCNPQ::Ciências Sociais Aplicadas::Direito